Translational researchers' training and development needs, preferences, and barriers: A survey in a National Institute for Health Research Biomedical Research Centre in the United Kingdom - Karen Bell; Syed Ghulam Sarwar Shah; Lorna R. Henderson; Vasiliki Kiparoglou (Wiley, 2022)
Abstract The objective was to identify translational researchers' training and development needs, preferences, and barriers to attending training. This cross‐sectional study involved an online questionnaire survey. The research population comprised a convenience sample of translational researchers and support staff (N = 798) affiliated with the National Institute for Health Research Oxford Biomedical Research Centre. The response rate was 24%. Of 189 respondents, 114 were women (60%) and 75 were men (40%). The respondents were mainly research scientists (31%), medical doctors and dentists (17%), and research nurses and midwives (16%). Many of the respondents had attended at least one training course in the last year (68%). Training in statistics and data analysis was the most common training received (20%). Leadership training was the most wanted training (25%). Morning was the most preferred time of training (60%). Half a day was the ideal duration of a training course (41%). The main teaching hospital site was the most preferred location of training (46%). An interactive workshop was the most favored delivery style of training (52%). Most common barriers to attending training were the lack of time (31%), work (21%) and clinical commitments (19%), and family and childcare responsibilities (14%). Some differences in training needs, preferences, and barriers were found by gender and role, though these were not statistically significant. Translational researchers want short, easily accessible, and interactive training sessions during the working day. The training needs, preferences, and barriers to attending training need to be considered while developing inclusive training programs in biomedical research settings.